ROME AND THE INDIAN OCEAN TRADE FROM AUGUSTUS TO THE EARLY THIRD CENTURY CE. - COBB, MATTHEW A. (Mnemosyne, Supplements, 2018)
In Rome and the Indian Ocean Trade from Augustus to the Early Third Century CE Matthew Adam Cobb examines the development of commercial exchange between the Mediterranean and the Indian Ocean worlds from the Roman annexation of Egypt (30 BCE) up to the early third century CE. Among the issues considered are the identities of those involved, how they organised and financed themselves, the challenges they faced (scheduling, logistics, security, sailing conditions), and the types of goods they traded. Drawing upon an expanding corpus of new evidence, Cobb aims to reassess a number of long-standing scholarly assumptions about the nature of Roman participation in this trade. These range from its chronological development to its economic and social impact.